JURIDICAL ANALYSIS OF GOOD HEALTH SERVICES IN INDONESIAN HEALTH LAW FROM AN ISLAMIC PERSPECTIVE - Wibowo, Rio Pradita (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2024)
When fulfilling the implementation of good health services, regulations governing health services are needed. Law Number 17 of 2023 concerning Health has regulated health services, but has the regulation been considered good from an Islamic perspective? This article aims to find out the regulations in the discussion of how health services in Law Number 17 of 2023, then juxtaposed with prophetic values based on an Islamic perspective. The method used is normative juridical with a type of literature study research conducted by collecting, studying and examining books, as well as related documents such as scientific journals. Regulations regarding health services have been regulated in Law No. 17 of 2023, but are incomplete due to the absence of implementing regulations. Islam views health services as a step towards the welfare of the ummah, not only Muslims, but focuses on citizens in a fair manner.